Parental attitudes to randomised controlled trials in primary dental care: A qualitative study - Heather Coventry; Anne Maguire; Elaine McColl; Catherine Haighton (PLoS ONE, 2026)
Background A clinical paedodontic randomised controlled trial (FiCTION) provided the opportunity to explore recruitment and retention challenges in The National Health Service (NHS) primary dental care settings. Purpose To investigate parental attitudes towards their child’s participation in a dental randomised controlled trial (RCT). Methods Parents whose child(ren) (aged 3–7 years) were participants in a dental RCT or who had been screened for the trial but did not participate were asked to consent to be contacted regarding completing a questionnaire and a semi-structured face-to-face qualitative interview. Using a purposive, maximum variation sampling strategy a subsample of parents who had completed the questionnaire study completed an interview. Data were coded using NVivo and the Framework Method of thematic analysis applied. Results The 18 parents consenting to an interview indicated positive attitudes towards research in primary dental care. There were no noticeable contrasting views of good dental health, or perceptions of facilitators and barriers thereof, between parents whose child(ren) were FiCTION participants and those whose child(ren) were not. Research involvement did not appear to be a major incentive to attend a particular practice, and while parents viewed research-active dental practices favourably, they did not always understand why their practice was research-active (especially for those not participating in FiCTION). Most FiCTION parents felt comfortable with the concept of trial withdrawal or requesting a change in treatment arm. However, parents did not always have complete knowledge or understanding of the research study in which they had been invited to participate. While FiCTION parents had overall greater understanding of research, concepts such as randomisation were hard for most parents to grasp. Conclusions Parents valued dental research in primary care but perceived it as complex and challenging. Further research should explore the best methods to achieve engagement with patients in primary dental care research.